Tunable photovoltaic effect and solar cell performance of self-doped perovskite SrTiO3 - Jin, K. X. (2013)
We report on the tunable photovoltaic effect of self-doped single-crystal SrTiO3 (STO), a prototypical perovskite-structured complex oxide, and evaluate its performance in Schottky junction solar cells. The photovaltaic characteristics of vacuum-reduced STO single crystals are dictated by a thin surface layer with electrons donated by oxygen vacancies. Under UV illumination, a photovoltage of 1.1 V is observed in the as-received STO single crystal, while the sample reduced at 750 °C presents the highest incident photon to carrier conversion efficiency. Furthermore, in the STO/Pt Schottky junction, a power conversion efficiency of 0.88% was achieved under standard AM 1.5 illumination at room temperature. This work establishes STO as a high-mobility photovoltaic semiconductor with potential of integration in self-powered oxide electronics.